Analisa Efesiensi Bahan Bakar Dan Dampak Lingkungan Emisi Gas Buang Pembangkit Listrik Tenaga Diesel (Pltd) Terhadap Pembangkit Listrik Mesin Gas (PLTMG) - marhaini, marhaini; Mardwita, Mardwita; Suranda, Arief (UNIVERSITAS MUHAMMADIYAH PALEMBANG, 2022)
The need for electrical energy is a primary human need at this time, the need for electricity is almost a necessity for both industry, offices, and the general public. The main problem of the power generation industry today is the use of oil as fuel for power generation which will increase the cost of electricity production. One of the government's efforts to reduce the use of fuel oil is to use oil fuel with the consideration that natural gas is more effective and efficient, its use is more practical and its emissions are more environmentally friendly when compared to solar power. From these problems arose the idea of calculating the efficiency between a diesel-fired power plant (PLTD) and a gas engine power plant (PLTMG) powered by LNG (Liquedfied Natural Gas) and the resulting emission measurement results. The study conducted an efficiency analysis by carrying out a 50% and 75% load test of installed capacity and analyzing its environmental friendliness by taking the emission test results.